2018
DOI: 10.1002/tox.22529
|View full text |Cite
|
Sign up to set email alerts
|

Butyl paraben promotes apoptosis in human trophoblast cells through increased oxidative stress‐induced endoplasmic reticulum stress

Abstract: Butyl paraben (BP) has antimicrobial effects and is widely used as a preservative in cosmetics, foods, and pharmaceuticals. It is also absorbed into various tissues of the human body. It is known that BP is measurable in maternal and fetal tissues during pregnancy, but the effects of BP on placental development, essential for maintaining normal pregnancy, are unclear. Therefore, we investigated the effect of BP on the proliferation, apoptosis, and invasiveness of human trophoblast cells, using an HTR8/SVneo ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 30 publications
(39 reference statements)
2
23
0
2
Order By: Relevance
“…Well-organized mitochondria with a homogenous distribution in the cytoplasm and high mitochondrial membrane potential are considered important for oocyte cytoplasmic maturation [20]. A previous study reported that BP had toxic effects on human trophoblast cells through oxidative stress-induced mitochondrial dysfunction [33]. In this study, BP-treated oocytes exhibited significantly higher aberrant mitochondrial distribution and had a significantly lower mitochondrial membrane potential, indicating that BP compromised mitochondrial function and cytoplasmic maturation.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Well-organized mitochondria with a homogenous distribution in the cytoplasm and high mitochondrial membrane potential are considered important for oocyte cytoplasmic maturation [20]. A previous study reported that BP had toxic effects on human trophoblast cells through oxidative stress-induced mitochondrial dysfunction [33]. In this study, BP-treated oocytes exhibited significantly higher aberrant mitochondrial distribution and had a significantly lower mitochondrial membrane potential, indicating that BP compromised mitochondrial function and cytoplasmic maturation.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, the GSH level in the oocyte reflects cytoplasmic maturation [31]. Previous studies reported that BP exerts oxidative stress by reducing the levels of non-enzymatic antioxidants, such as GSH, and the levels of enzymatic antioxidants, such as superoxide dismutase, catalase, and GSH transferase, which results in cellular apoptosis [32][33][34]. In this study, BP-treated oocytes showed significantly increased ROS levels and decreased GSH levels, indicating that BP induced oxidative stress during oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…This may have been caused by the accumulation of Cyclin B1 and the reduction in Cyclin D1 due to ethylparaben ( Figures 3 and 4). Previous studies have demonstrated that different types of parabens induce cell death in different cell types (Perez Martin et al 2010;Dubey et al 2017;Yang et al 2018). However, there is no report regarding the adverse effect of ethylparaben on cellular lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…The placenta is the location where gas and nutrient exchange occurs and where metabolic products are eliminated between the mother and the fetus. As part of the main placental structure, invasion of trophoblast cells into the endometrium is an important physiological process in the formation of the placenta ( 35 , 36 ). Studies have shown that extravillous trophoblast cells invade into the uterine decidua and myometrial spiral artery, where they gradually replace the endothelial cell layer and part of the smooth muscle tissue in the maternal spiral arteries, resulting in thickened blood vessels to provide sufficient blood supply to the fetus ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%